2020
DOI: 10.3389/fphar.2020.01211
|View full text |Cite
|
Sign up to set email alerts
|

Target Analysis and Mechanism of Podophyllotoxin in the Treatment of Triple-Negative Breast Cancer

Abstract: Background: As the original compound of many podophyllotoxin derivatives, podophyllotoxin has a beneficial antitumor effect. The mechanism of podophyllotoxin activity in triple-negative breast cancer still needs to be explored. Methods: We used cell proliferation assay, scratch and transwell experiments, and cell cycle and apoptosis analyses to observe the intervention effect of podophyllotoxin on breast cancer. Furthermore, we analyzed the differences between GSE31448, GSE65194, and GSE45827 in the Gene Expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 55 publications
(59 reference statements)
0
16
0
Order By: Relevance
“…It led to the production of ROS and γ-H2AX and activated the ATM/p53/p21 pathway to trigger DNA damage response in human breast cancer cells, and also induced mitochondrial apoptosis and cell cycle arrest. Zhang et al (2020) comprehensively analyzed the molecular mechanism of PTOX on TNBC, and they suggested that PLK1 may be a downstream key gene. Furthermore, many drug delivery system (DDS)-based products were developed to improve aqueous solubility and reduce the side effects of PTOX.…”
Section: Breast Cancermentioning
confidence: 99%
“…It led to the production of ROS and γ-H2AX and activated the ATM/p53/p21 pathway to trigger DNA damage response in human breast cancer cells, and also induced mitochondrial apoptosis and cell cycle arrest. Zhang et al (2020) comprehensively analyzed the molecular mechanism of PTOX on TNBC, and they suggested that PLK1 may be a downstream key gene. Furthermore, many drug delivery system (DDS)-based products were developed to improve aqueous solubility and reduce the side effects of PTOX.…”
Section: Breast Cancermentioning
confidence: 99%
“…For example, the finding reported by Zhang showed that CentiScape and MCODE plug‐ins were used to mine the functional modules associated with the Mycobacterium tuberculosis infection process 37 . The investigation reported by Zhang W identified the Key Genes associated with breast cancer using plug‐in CentiScape and MCODE 16 . Consistent findings were reported by Zhang, indicating that the MCODE plug‐in was utilized to screen hub genes and gene modules in the PPI network, obtaining the potential key genes for colorectal cancer (CRC) liver metastasis 38 .…”
Section: Discussionmentioning
confidence: 99%
“…The genes at the top of the degree distribution (≥ 95% percentile) in the significantly perturbed networks were defined as central genes 15 . Moreover, cluster analysis was performed by the Cytoscape 3.6.1 software plug‐in molecular complex detection (MCODE), which the best protein module can be selected by the score of the node 16 . Besides, the targets including emodin were imported into the STITCH database (http://stitch.embl.de/,ver.5.0), 17 identifying the essential target gene directly linked to the emodin.…”
Section: Methodsmentioning
confidence: 99%
“…Whereas the anticancer activity of PT is mainly from the inhibition of DNA topoisomerase II and microtubule assembly ( Sathish et al ., 2018 ), studies are revealing more molecular targets of PT. PT was shown to inhibit the growth of triple-negative breast cancer cells such as MDA-MB-231 ( Zhang et al ., 2020 ). We recently reported that PT inhibited the growth of gefitinib-resistant non-small cell lung cancer cells by targeting c-MET ( Oh et al ., 2021 ).…”
Section: Discussionmentioning
confidence: 99%